Maternal Eating and Physical Activity Strategies and their Relation with Children's Nutritional Status - Yolanda Flores-Peña; Rosario Edith Ortiz-Félix; Velia Margarita Cárdenas-Villarreal; Hermelinda Ávila-Alpirez; Corina Mariela Alba-Alba; Roandy Gaspar Hernández-Carranco (Universidade de São Paulo, 2014)
OBJECTIVES: to describe the maternal eating and physical activity strategies (monitoring, discipline, control, limits and reinforcement) [MEES]; to determine the relation between MEES and the child's nutritional status [body mass index (BMI) and body fat percentage (BFP)]; to verify whether the MEES differ according to the child's nutritional status.METHOD: participants were 558 mothers and children (3 to 11 years of age) who studied at public schools. The Parental Strategies for Eating and Activity Scale (PEAS) was applied and the child's weight, height and BFP were measured. For analysis purposes, descriptive statistics were obtained, using multiple linear regression and the Kruskal-Wallis test.RESULTS: the highest mean score was found for reinforcement (62.72) and the lowest for control (50.07). Discipline, control and limits explained 12% of the BMI, while discipline and control explained 6% of the BFP. Greater control is found for obese children (χ2=38.36, p=0.001) and greater reinforcement for underweight children (χ2=7.19, p<0.05).CONCLUSIONS: the mothers exert greater control (pressure to eat) over obese children and greater recognition (congratulating due to healthy eating) in underweight children. Modifications in parental strategies are recommended with a view to strengthening healthy eating and physical activity habits.